Oxford dictionary of phrasal verbs - Cowie, A P (Oxford University Press, 1993)
This new edition has benfited from generous help and advice from several sources. We woud particularly like to thank Oxford University Press for kindly allowing us to draw on the Oxford Corpus fo the English Languaje for numreous up-ti date items and examples.